Irving Smith - SJSU Special Collections & Archives::::::::: (2022)
The University Archives has records of a student named Irving Smith on the track team in 1942. We also have records of a track athlete named Bill Smith, sometimes called Billy Smith. SJSU Athletics has records of a student named Bill I. Smith on the Track Team in 1942. If we are correct to assume that Bill I. Smith and Irving Smith are the same person, then it appears that he attended San Jose State College in 1942. He was a member of the track team and received a Service Award for Track in May of 1942. Smith may have also been a member of the campus Forensic Squad and participated in debates and speeches as part of that club. He was called into service with the Army Reserves during World War II. In 1946 the Spartan Daily reported that Bill Smith was married and working in Southern California.